Wired for learning - Lasarenko, Jane. 4 0 16; 5 (Indianapolis, IN : Que, 1997)
Discusses how to teach using Internet-based technologies, showing how to construct projects with step-by-step instructions, implement cooperative learning strategies, teach students to write on the Web, and transform students into active learners with distance-learning teaching methods.
Harness the power of the Internet for education--Cover;Includes index.
Professional;Professional
Keywords: 2 -- 0; 6; Computer network resources.;Computer network resources.;Computer assisted instruction. -- Internet in education.;Teaching;Education;Computer-assisted instruction.;Internet.;Education; 20; 2